NGO's and post-conflict recovery : the Leitana Nehan Women's Development Agency, Bougainville - Hakena, Helen; Ninnes, Peter, 1960-; Jenkins, Bert (Asia Pacific Press : ANU E Press, 2006)
The book will make a unique contribution to understanding the role of NGOs in promoting peace, gender and development in the South West Pacific by recording the story of the Leitana Nehan Women's Development Agency. Australian authors.